Post a New Question

solve using cramer's rule

posted by on .

solve using cramer's rule
3x+4y=-1
5x-2y=4

  • solve using cramer's rule - ,

    First calculate the determinant D of
    3 4
    5 -2
    =3*(-2)-4*5=-26

    Replace the first column by the RHS,and calculate determinant D1
    -1 4
    4 -2
    =(-1)(-2)-4*4
    =-14

    Replace the column with the RHS and calculate determinant D2
    3 -1
    5 4
    =3*4-(-1)*5
    =17
    x=D1/D=-14/-26=7/13
    y=D2/D=17/-26=-17/26

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question